2001
DOI: 10.3748/wjg.v7.i3.340
|View full text |Cite
|
Sign up to set email alerts
|

Expression of nuclear factor-κB in hepatocellular carcinoma and its relation with the X protein of hepatitis B virus

Abstract: Expression of nuclear factor-κB in hepatocellular carcinoma and its relation with the X protein of hepatitis B virus. World J Gastroenterol, 2001;7(3):340-344 Abstract AIM In this study we investigated the relationship of the X protein of HBV and nuclear factor-κ κ κ κ κB (NF-κ κ κ κ κB) and the expression of NF-κ κ κ κ κB in human hepatocellular carcinoma tissues. METHODS Immunohistochemistry SP method was used to detect the expression of NF-κ κ κ κ κB and the X protein of HBV in human hepatocellular carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Because p65 is one of the most common members in NF-κB family, and IκB-α is the most important inhibitor, detection of p65 and IκB-α expression can reflect the state of NF-κB metabolism. In our test, low expression rate of p65 and weakly positive expression of IκB-α represented the nonactive state of NF-κB in non-cancerous tissues, but the activation enhancement of NF-κB in HCC was in accord with the previous reports [23,24] . The expression of IκB-α in HCC and its corresponding liver tissue has not been reported yet.…”
Section: Discussionsupporting
confidence: 79%
“…Because p65 is one of the most common members in NF-κB family, and IκB-α is the most important inhibitor, detection of p65 and IκB-α expression can reflect the state of NF-κB metabolism. In our test, low expression rate of p65 and weakly positive expression of IκB-α represented the nonactive state of NF-κB in non-cancerous tissues, but the activation enhancement of NF-κB in HCC was in accord with the previous reports [23,24] . The expression of IκB-α in HCC and its corresponding liver tissue has not been reported yet.…”
Section: Discussionsupporting
confidence: 79%
“…Unlike other types of cancer, HCC has been found usually preceded by chronic inflammation due to viral infection [34][35][36][37] . Matsuyama et al [11] reported that the frequency of mtDNA mutations was markedly increased in both noncancerous and cancerous liver specimens compared with control liver tissue.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that the products of certain NF-B target genes inhibit apoptosis, regulate cell cycle progression, and govern invasion and metastasis (8 -10). NF-B activation has also been implicated in the development of hepatocellular carcinoma (HCC) related to hepatitis B virus (HBV) infection (11,12).…”
Section: Introductionmentioning
confidence: 99%